Clinical and biological relevance of genetic alterations in pediatric T‐cell acute lymphoblastic leukemia in Taiwan. Issue 1 (2nd October 2018) - Yeh, Ting‐Chi; Liang, Der‐Cherng; Liu, Hsi‐Che; Jaing, Tang‐Her; Chen, Shih‐Hsiang; Hou, Jen‐Yin; Yang, Chao‐Ping; Huang, Ying‐Jung; Yao, Hsien‐Wen; Huang, Ting‐Yu; Lin, Tung‐Huei; Shih, Lee‐Yung
Abstract: Background: The leukemogenesis of T‐cell acute lymphoblastic leukemia (T‐ALL) involves multistep processes of genetic alterations. We aimed to determine the genetic alterations including common fusion transcripts, overexpression of T‐cell transcription factor oncogenes, and deletion or mutation of targeted genes in pediatric T‐ALL in Taiwan as well as their impact on outcomes in those treated with the Taiwan Pediatric Oncology Group‐ALL‐2002 protocol. Procedure: Between 1995 and 2015, bone marrow samples obtained from 102 children aged <18 years consecutively diagnosed with T‐ALL were examined. Thirty‐two genetic alterations were examined by reverse transcription polymerase chain reaction (PCR) assays—PCR‐based assays—followed by direct sequencing, real time quantitative PCR with TaqMan assays, or multiplex ligase probe amplification. Results: TAL1 overexpression, CDKN2A / 2B deletions, and NOTCH1 mutation were the most frequent aberrations while none had NF1, SUZ12 deletion, JAK1 or JAK2 mutations, or NUP214‐ABL1 fusion in our cohort. The most frequent cooperating occurrence of genetic alterations included CDKN2A/2B and MTAP, MTAP and CDKN2B, LEF1 and PTPN2, and HOX11L2 and PHF6 mutation/deletion. NOTCH1 mutations conferred a favorable overall survival, whereas SIL‐TAL1 fusion, TAL overexpression, LEF1 deletion, and PHF 6 deletion/mutation were associated with an inferior outcome. By multivariate analysis, PHF6 mutation/deletion was the only independent predictor for inferior overall survival. Conclusions: The present study showed that the frequencies of genetic alterations in Taiwanese children with T‐ALL differed considerably from those reported in Western countries. PHF6 mutation/deletion was an independently adverse predictor.